Composite resin composition for automobile interior material and automobile interior material produced using the composite resin composition

By optimizing the material composition of the composite resin composition, the problems of insufficient heat and chemical resistance of existing automotive interior materials are solved, and the balance between mechanical properties, fluidity and light resistance is achieved, and excellent product reliability and appearance quality are provided.

CN115605539BActive Publication Date: 2025-05-02LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280003486.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-02-24
Filing Date
2022-02-25
Publication Date
2025-05-02
Estimated Expiration
2042-02-25

AI Technical Summary

Technical Problem

The existing automotive interior materials have insufficient heat and chemical resistance, making it difficult to meet the balance between mechanical properties, fluidity and light resistance.

Method used

Using a composite resin composition, comprising 15-20% of the first vinyl cyano compound-conjugated diene compound-aromatic vinyl compound copolymer, 9-15% of the second vinyl cyano compound-conjugated diene compound-aromatic vinyl compound copolymer, 32-40% of the aromatic vinyl compound-vinyl cyano compound copolymer and 29-37% of the polyester resin, the material performance is improved by optimizing the material composition.

Benefits of technology

The composite resin composition significantly improves heat and chemical resistance, satisfies the balance between mechanical properties, flowability and light resistance, and provides excellent product reliability and appearance quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003884813530000151
    Figure BDA0003884813530000151
  • Figure BDA0003884813530000201
    Figure BDA0003884813530000201
  • Figure BDA0003884813530000211
    Figure BDA0003884813530000211
Patent Text Reader

Abstract

The present invention relates to a composite resin composition for automotive interior products and an automotive interior product manufactured using the composite resin composition. More specifically, the composite resin composition for automotive interior products according to the present invention comprises optimized raw materials, thereby providing improved heat resistance and chemical resistance. Therefore, the composite resin composition for automotive interior products according to the present invention can satisfy the balance between physical properties such as mechanical properties, fluidity and light resistance, and provide excellent product reliability and appearance quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]

[0002] This application claims the priority of Korean Patent Application No. 10-2021-0059760 filed in the Korean Intellectual Property Office on May 10, 2021, and Korean Patent Application No. 10-2022-0024264 filed again in the Korean Intellectual Property Office on February 24, 2022 based on the priority of the patent, and the disclosures of each of these two patent applications are incorporated into this specification by reference.

[0003] The present invention relates to a composite resin composition for an automotive interior product and an automotive interior product manufactured using the composite resin composition, and more particularly to a composite resin composition for an automotive interior product, wherein raw materials contained in the composite resin composition are optimized so that heat resistance and chemical resistance are improved, thereby satisfying a balance between physical properties such as mechanical properties, fluidity and light resistance, and providing excellent product reliability and appearance quality; and an automotive interior product manufactured using the composite resin composition. Background Art

[0004] As conventional automotive interior product materials, there are acrylonitrile-butadiene-styrene (ABS) resin, a composite resin prepared by mixing polycarbonate (PC) resin and acrylonitrile-butadiene-styrene (ABS) resin, a composite resin prepared by mixing polycarbonate (PC) resin and acrylate-styrene-acrylonitrile (ASA) resin, a composite resin prepared by mixing polycarbonate (PC) resin and polyester resin, etc. These materials have excellent physical properties and are therefore used in various automotive interior parts.

[0005] However, since acrylonitrile-butadiene-styrene resin (ABS) has poor heat resistance, there are limitations in its application to electronic components or automotive interior products. In addition, when polycarbonate resin (PC) is mixed with acrylate-styrene-acrylonitrile resin (ASA), due to the amorphous nature of the material itself, chemical resistance is weak, which causes cracks in chemical products commonly used in automobiles.

[0006] Therefore, it is necessary to develop a material for automotive interior products having improved heat resistance and chemical resistance so as to satisfy a physical property balance between mechanical properties, light resistance, etc.

[0007] [Related technical literature]

[0008] [Patent Document]

[0009] Korean Patent Application Publication No. 2018-0068566 (published on June 22, 2018) Summary of the invention

[0010] Technical issues

[0011] Therefore, the present invention is made in view of the above problems, and an object of the present invention is to provide a composite resin composition for automotive interior products, wherein the composite resin composition comprises optimized materials so that the production cost can be reduced, and the composite resin composition can be used for unpainted products, thereby providing excellent economic feasibility. In addition, it is possible to improve heat resistance and chemical resistance, meet the balance between physical properties such as mechanical properties, fluidity and light resistance, and provide excellent product reliability and appearance quality.

[0012] Another object of the present invention is to provide an automobile interior product manufactured using the composite resin composition for automobile interior products.

[0013] The above-mentioned objects and other objects can be achieved by the present disclosure described below.

[0014] Technical Solution

[0015] According to one aspect of the present invention, the above-mentioned object and other objects can be achieved by providing a composite resin composition, the composite resin composition comprising:

[0016] 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 wt % to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 wt % to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 wt % to 37 wt % of a polyester resin, wherein the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer.

[0017] A weight ratio of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer to the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be 1:1.37 to 1.66.

[0018] The polyester resin may be one or more selected from polybutylene terephthalate (PBT), polyethylene adipate (PEA), polybutylene succinate (PBS), polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), and polyethylene naphthalate (PEN).

[0019] The composite resin composition may have an L* value of 14.00 or less, the L* value being obtained by measuring light reflected by a sample obtained by SCE using a LAB colorimetric system.

[0020] The first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may include: 40 wt % to 80 wt % of a diene rubber polymer having an average particle size of 100 nm to 500 nm, 10 wt % to 40 wt % of an aromatic vinyl compound, and 1 wt % to 20 wt % of a vinyl cyanide compound.

[0021] The second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may include 5 to 20 wt % of a diene rubber polymer having an average particle size of 800 to 10,000 nm, 50 to 85 wt % of an aromatic vinyl compound, and 10 to 30 wt % of a vinyl cyanide compound.

[0022] The aromatic vinyl compound-vinyl cyanide compound copolymer may include 71 to 72 wt % of the aromatic vinyl compound and 28 to 29 wt % of the vinyl cyanide compound, and have a weight average molecular weight of 130,000 to 180,000 g / mol.

[0023] The content of the vinyl cyanide compound included in the aromatic vinyl compound-vinyl cyanide compound copolymer may be 26 wt % or more based on the total weight of the copolymer.

[0024] The polyester resin may have an intrinsic viscosity of 1.05 dl / g or more.

[0025] The composite resin composition may have a flow index measured at 250° C. under a load of 5 kg according to ISO 1133 of 25 g / 10 min or more.

[0026] The Izod impact strength of the composite resin composition measured at 23° C. according to ISO 180 / 1A may be 14 kJ / m 2 above.

[0027] The flexural modulus of a 1 / 8 inch test specimen manufactured using the composite resin composition measured at a speed of 2 mm / min according to ISO 178 may be 1950 MPa or more.

[0028] The composite resin composition may have a high-load heat resistance of 75° C. or more measured at 1.82 MPa according to ISO 75.

[0029] According to another aspect of the present invention, there is provided a composite resin composition comprising:

[0030] 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 wt % to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 wt % to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 wt % to 37 wt % of a polyester resin, wherein the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, and the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer is 27 wt % to 29 wt % based on the total weight of the copolymer, and the intrinsic viscosity of the polyester resin is 1.05 dl / g or more.

[0031] According to another aspect of the present invention, there is provided a method for preparing a composite resin composition, the method comprising:

[0032] 15 to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 to 37 wt % of a polyester resin are fed into an extruder, followed by melt-mixing and extrusion steps, wherein the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer.

[0033] According to another aspect of the present invention, there is provided a method for preparing a composite resin composition, the method comprising:

[0034] A step of feeding 15 to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 to 37 wt % of a polyester resin into an extruder, followed by melt-kneading and extruding, wherein the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, and the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer is 27 to 29 wt % based on the total weight of the copolymer, and the intrinsic viscosity of the polyester resin is 1.05 dl / g or more.

[0035] According to another aspect of the present invention, there is provided an automotive interior product manufactured using the composite resin composition.

[0036] The automotive interior product may be a floor console tray or a cup holder.

[0037] Beneficial Effects

[0038] The composite resin composition according to the present invention can be molded into an automobile interior product.

[0039] In addition, the automotive interior product has improved heat resistance and chemical resistance, thereby having excellent molding properties while satisfying a balance between physical properties such as mechanical properties, fluidity and light resistance. Therefore, the appearance quality is improved.

[0040] Therefore, the composite resin composition according to the present invention can be particularly applied to the field of automotive interior products, including floor control seat front trays and cup holders. DETAILED DESCRIPTION

[0041] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0042] The terms or words used in this specification and the appended claims should not be understood as being limited to the ordinary meanings or the meanings in the dictionary, and should be understood as meanings and concepts consistent with the technical concept of the present invention, considering that the inventor can appropriately define the concepts of the terms in order to describe the invention in the best manner.

[0043] In the present disclosure, unless defined otherwise, "comprising" may be defined as "aggregating to comprise" or "comprising as a unit from...".

[0044] In this disclosure, the weight % of a unit, the weight % of a unit, or the weight % of a block in a polymer may refer to the weight % of the derived monomer.

[0045] In addition, in the present disclosure, the weight % of the unit in the polymer, the weight % of the unit or the weight % of the block can be measured by the method commonly used in the technical field to which the present invention belongs. As another method, under the premise that all monomers are polymerized, the content of the added monomer can be defined as the content of the unit in the prepared polymer, for example.

[0046] Unless otherwise stated, all numerals, numerical values ​​and / or expressions of the amount of the expression composition, reaction conditions, polymer composition and formulation used in the present disclosure are approximate values, reflecting the various uncertainties due to the measurements performed, to obtain numerical values ​​from essentially different values. Therefore, it should be understood that the term "about" is modified in all cases. In addition, when a numerical range is disclosed in the present disclosure, unless otherwise stated, such a range is continuous and includes all values ​​from the minimum value to the maximum value of the range. In addition, when such a range refers to an integer, unless otherwise stated, all integers from the minimum value to the maximum value are included.

[0047] In the present disclosure, when a variable is expressed as a range, it is understood that the variable includes all values ​​within the range, including the endpoints of the range. For example, it is understood that the range of "5 to 10" includes values ​​of 5, 6, 7, 8, 9, and 10, and any subranges of 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., and any values ​​between the integers falling within the recited ranges, such as 5.5 to 8.5 and 6.5 to 9, etc. In addition, it is understood that the range of 10% to 30% includes values ​​of 10%, 11%, 12%, 13%, etc. and includes all integers up to 30%, as well as any values ​​between the valid integers within the range of the range, such as 10.5%, 15.5%, 25.5%, etc.

[0048] The present inventors have confirmed that an automotive interior product prepared using a composite resin composition comprising a polyester resin, an emulsion-polymerized copolymer, a bulk-polymerized copolymer, etc. exhibits improved heat resistance and chemical resistance, satisfies a balance between physical properties such as mechanical properties, fluidity, and light resistance, and provides excellent product reliability and appearance quality. In addition, the present inventors have completed an automotive interior product material having excellent molding properties and appearance quality while satisfying a balance between physical properties such as mechanical properties, fluidity, and light resistance, and does not require painting.

[0049] Composite resin composition

[0050] The composite resin composition according to one embodiment of the present invention comprises: 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 wt % to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 wt % to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 wt % to 37 wt % of a polyester resin,

[0051] Wherein, the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer. In this case, compared with the existing composite resin prepared by mixing polycarbonate resin (PC) and acrylate-styrene-acrylonitrile (ASA), the composite resin composition according to one embodiment of the present invention can reduce production costs. In addition, the composite resin composition can be used for unpainted products, thereby having excellent economic feasibility. In addition, the composite resin composition has improved heat resistance and chemical resistance, thereby satisfying the balance between physical properties such as mechanical properties, fluidity and light resistance, and realizing automotive interior products with excellent product reliability and appearance quality.

[0052] The polyester resin according to one embodiment of the present invention is a crystalline material, and therefore, a composite resin composition including the polyester resin has moldability, and an automotive interior product manufactured using the composite resin composition has chemical resistance.

[0053] The polyester resin may include, but is not limited to, one or more selected from polybutylene terephthalate (PBT), polyethylene adipate (PEA), polybutylene succinate (PBS), polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT) and polyethylene naphthalate (PEN). As a specific example, polybutylene terephthalate (PBT) may be used. By using polybutylene terephthalate (PBT), when injection molding is performed to have a crystalline structure, the fluidity of the composite resin composition is improved while preventing the penetration of chemicals introduced from the outside, thereby providing excellent appearance quality.

[0054] The intrinsic viscosity of the polyester resin may be, for example, 1.05 dl / g or more, 1.1 dl / g or more, or 1.1 dl / g to 1.3 dl / g. When the intrinsic viscosity is too low and outside the range, the effect of enhancing physical properties is reduced, so that the effect of improving chemical resistance is not significant. When the intrinsic viscosity is too high, the molding performance is reduced, so that there may be problems with the appearance of the parts.

[0055] In the present disclosure, when measuring the intrinsic viscosity, unless otherwise specified, the sample to be measured is completely dissolved in a dichloromethane solvent having a concentration of 0.05 g / ml, and then filtered using a filter to obtain a filtrate. Then, using the obtained filtrate, the intrinsic viscosity is measured using an Ubbelohde viscometer at 20°C.

[0056] The polyester resin may be included in an amount of 29 to 37 wt %, specifically 33 to 37 wt %, based on 100 wt % of the total composite resin (polyester resin + first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + aromatic vinyl compound-vinyl cyanide compound copolymer). When the polyester resin content is lower than the range, an automotive interior product prepared using the composite resin composition including the polyester resin may be cracked. When the polyester resin content is greater than the range, the rigidity and heat resistance of the automotive interior product prepared using the composite resin composition including the polyester resin are reduced.

[0057] The styrene-based resin used in the present invention may preferably be composed of a ternary system prepared by mixing a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, and an aromatic vinyl compound-vinyl cyanide compound copolymer. When the styrene-based resin is included together with the above-mentioned polyester resin, the chemical resistance of the composite resin composition including them is greatly affected, and the automotive interior product manufactured using the composite resin composition exhibits improved chemical resistance.

[0058] In the present disclosure, “styrene-based resin” refers to a styrene-based resin well known in the technical field to which the present invention pertains, and may refer to, for example, a resin including a unit derived from an aromatic vinyl compound.

[0059] In the present disclosure, the sum of the weights of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the weight of the polyester resin, the reduction in physical properties caused by the polyester resin is compensated, and an automotive interior product prepared using the composite resin composition including the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer exhibits improved impact resistance and mechanical properties.

[0060] In the present disclosure, the sum of the weights of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the aromatic vinyl compound-vinyl cyanide compound copolymer is greater than the weight of the polyester resin, and the flexural modulus and heat resistance are improved.

[0061] As a specific example, preferably, based on 100 parts by weight of the above polyester resin, the total content of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the aromatic vinyl compound-vinyl cyanide compound copolymer is specifically 145 parts by weight to 209 parts by weight, more preferably 150 parts by weight to 205 parts by weight, more preferably 160 parts by weight to 205 parts by weight, and most preferably 165 parts by weight to 203 parts by weight. Within this range, the reduction in physical properties due to the polyester resin is compensated, and the automotive interior product prepared using the composite resin composition including the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the aromatic vinyl compound-vinyl cyanide compound copolymer exhibits improved impact resistance and mechanical properties.

[0062] The weight ratio of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer to the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be, for example, 1: 1.37 to 1.66, preferably 1: 1.4 to 1.63. Within this range, the reduction in physical properties due to the polyester resin is compensated, and an automotive interior product prepared using the composite resin composition comprising the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer exhibits improved mechanical properties such as impact resistance and flexural modulus, improved flow index, and improved heat resistance under high load.

[0063] The first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer according to one embodiment of the present invention may contain: 40% to 80% by weight of a diene rubber polymer having an average particle size of 100nm to 500nm; 10% to 40% by weight of an aromatic vinyl compound; and 1% to 20% by weight of a vinyl cyanide compound. Preferably, the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be a graft copolymer prepared by emulsion polymerization of 50% to 70% by weight of a diene rubber polymer, 20% to 35% by weight of an aromatic vinyl compound, and 1% to 15% by weight of a vinyl cyanide compound, more preferably a graft copolymer prepared by emulsion polymerization of 55% to 65% by weight of a conjugated diene compound, 25% to 35% by weight of an aromatic vinyl compound, and 5% to 15% by weight of a vinyl cyanide compound. When the content of the conjugated diene compound constituting the diene rubber polymer is too small and outside the range, the impact resistance is reduced. On the other hand, when the content of the conjugated diene compound constituting the diene rubber polymer is too high, the rigidity (elastic modulus) is reduced. In addition, when the content of the vinyl cyanide compound is too little, the effect of enhancing the rigidity is not significant. On the other hand, when the content of the vinyl cyanide compound is too high, the impact resistance is reduced.

[0064] The conjugated diene compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may include, for example, butadiene, but is not limited to a specific conjugated diene compound. In addition, the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be, for example, selected from one or more of styrene, α-methylstyrene, α-ethylstyrene and p-methylstyrene, preferably styrene. In addition, the vinyl cyanide compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be, for example, selected from one or more of acrylonitrile and methacrylonitrile, preferably acrylonitrile.

[0065] Based on 100 wt % of the total composite resin composition (polyester resin + first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + aromatic vinyl compound-vinyl cyanide compound copolymer), the content of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be 16 wt % to 20 wt %, specifically 17 wt % to 19 wt %. When the content of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is too low, the automotive interior product prepared using the composite resin composition containing the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer exhibits reduced impact resistance. On the other hand, when the content of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is too high, the automotive interior product prepared using the composite resin composition containing the copolymer exhibits reduced rigidity.

[0066] That is, since the composite resin composition according to one embodiment of the present invention includes 16 wt % to 20 wt % of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer prepared by polymerizing the compounds in a specific content, an automotive interior product manufactured using the composite resin composition exhibits balanced impact resistance, rigidity, heat resistance, and chemical resistance.

[0067] The second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer according to one embodiment of the present invention may contain: 5 wt % to 20 wt % of a diene rubber polymer having an average particle size of 800 nm to 10,000 nm; 50 wt % to 85 wt % of an aromatic vinyl compound; and 10 wt % to 30 wt % of a vinyl cyanide compound. The second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer according to one embodiment of the present invention may preferably be a copolymer prepared by bulk polymerization of 5 wt % to 15 wt % of a diene rubber polymer, 57 wt % to 75 wt % of an aromatic vinyl compound, and 12 wt % to 28 wt % of a vinyl cyanide compound, and more preferably a copolymer prepared by bulk polymerization of 10 wt % to 15 wt % of a conjugated diene compound, 55 wt % to 75 wt % of an aromatic vinyl compound, and 15 wt % to 25 wt % of a vinyl cyanide compound. When the content of the conjugated diene compound constituting the diene rubber polymer is too small and outside the range, the impact resistance is reduced. On the other hand, when the content of the conjugated diene compound constituting the diene rubber polymer is too high, the rigidity (elastic modulus) is reduced. In addition, when the content of the vinyl cyanide compound is too little, the effect of enhancing the rigidity is not significant. On the other hand, when the content of the vinyl cyanide compound is too high, the impact resistance is reduced.

[0068] The conjugated diene compound, aromatic vinyl compound and vinyl cyanide compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be the same as the conjugated diene compound, aromatic vinyl compound and vinyl cyanide compound contained in the above-mentioned first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer.

[0069] Based on a total of 100 wt % of the composite resin composition (polyester resin + first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + aromatic vinyl compound-vinyl cyanide compound copolymer), the content of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be 10 wt % to 14 wt %, specifically 11 wt % to 13 wt %. When the content of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is too low, the appearance of an automotive interior product injection molded using the composite resin composition containing the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer may be deteriorated. On the other hand, when the content of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is too high, an automotive interior product prepared using the composite resin composition containing the copolymer exhibits reduced fluidity.

[0070] That is, since the composite resin composition according to one embodiment of the present invention includes 10 wt % to 14 wt % of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer prepared by polymerizing the compounds in a specific content range, an automotive interior product manufactured using the composite resin composition can exhibit balanced impact resistance, rigidity, heat resistance, and chemical resistance.

[0071] The aromatic vinyl compound-vinyl cyanide compound copolymer according to one embodiment of the present invention may be a copolymer containing 26% by weight or more of a vinyl cyanide compound and 74% by weight or less of an aromatic vinyl compound. Preferably, the aromatic vinyl compound-vinyl cyanide compound copolymer according to one embodiment of the present invention may be a copolymer containing 26% by weight to 29% by weight of a vinyl cyanide compound and 71% by weight to 74% by weight of an aromatic vinyl compound. More preferably, the aromatic vinyl compound-vinyl cyanide compound copolymer according to one embodiment of the present invention may be a copolymer containing 27% by weight to 29% by weight of a vinyl cyanide compound and 71% by weight to 73% by weight of an aromatic vinyl compound. More preferably, the aromatic vinyl compound-vinyl cyanide compound copolymer according to one embodiment of the present invention may be a copolymer containing 28% by weight to 29% by weight of a vinyl cyanide compound and 71% by weight to 72% by weight of an aromatic vinyl compound. When the content of the vinyl cyanide compound is too little and outside the range, the effect of enhancing rigidity is not significant. On the other hand, when the content of the vinyl cyanide compound is too high, impact resistance is reduced.

[0072] The aromatic vinyl compound and the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer may be the same as the aromatic vinyl compound and the vinyl cyanide compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer.

[0073] Based on a total of 100 wt % of the composite resin composition (polyester resin + first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer + aromatic vinyl compound-vinyl cyanide compound copolymer), the content of the aromatic vinyl compound-vinyl cyanide compound copolymer may be 32 wt % to 40 wt %, specifically 33 wt % to 37 wt %. When the content of the aromatic vinyl compound-vinyl cyanide compound copolymer is too low, an automotive interior product prepared using the composite resin composition comprising the aromatic vinyl compound-vinyl cyanide compound copolymer exhibits reduced flexural modulus. On the other hand, when the content of the aromatic vinyl compound-vinyl cyanide compound copolymer is too high, an automotive interior product prepared using the composite resin composition comprising the copolymer exhibits reduced heat resistance.

[0074] That is, since the composite resin composition according to one embodiment of the present invention includes 30 wt % to 38 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer prepared by polymerizing the compounds in a specific content range, an automotive interior product manufactured using the composite resin composition exhibits balanced impact resistance, rigidity, heat resistance, and chemical resistance.

[0075] The weight average molecular weight of the aromatic vinyl compound-vinyl cyanide compound copolymer may be preferably 130,000 g / mol to 180,000 g / mol, more preferably 130,000 g / mol to 160,000 g / mol, and more preferably 130,000 g / mol to 150,000 g / mol. Within this range, heat resistance and the like are excellent.

[0076] In the present disclosure, unless otherwise defined, weight average molecular weight can be measured using gel permeation chromatography (GPC, Water Breeze). As a specific example, weight average molecular weight can be measured by gel permeation chromatography (GPC, Water Breeze) using tetrahydrofuran (THF) as eluent. In this case, weight average molecular weight is obtained as a relative value relative to a polystyrene (PS) standard sample. As a specific measurement example, the weight-average molecular weight can be measured under the following conditions: solvent: THF, column temperature: 40°C, flow rate: 0.3 ml / min, sample concentration: 20 mg / ml, injection volume: 5 μl, chromatographic column model: 1×PLgel 10 μm MinMix-B (250×4.6 mm) + 1×PLgel 10 μm MinMix-B (250×4.6 mm) + 1×PLgel 10 μm MinMix-B Guard (550×4.6 mm), equipment name: Agilent 1200 series system, refractive index detector: Agilent G1362 RID, RI temperature: 35°C, data processing: Agilent ChemStation S / W, test method (Mn, Mw, PDI): OECD TG 118.

[0077] In order to improve the fluidity of the composite resin composition according to one embodiment of the present invention, to prevent it from being decomposed by high temperature or light, and to supplement chemical resistance, appropriate additives may be further included.

[0078] Specifically, one or more additives selected from lubricants, heat stabilizers, and ultraviolet absorbers may be further included.

[0079] The lubricant is not particularly limited as long as it can ensure easy extraction and fluidity of an injection screw for manufacturing an automotive interior product using a composite resin composition including the lubricant. Preferably, the lubricant may include vinyl bisstearamide, polyethylene wax, or a combination thereof.

[0080] The lubricant may be present in an amount of 0.01 to 10 parts by weight, specifically 0.1 to 3 parts by weight, based on 100 parts by weight of the composite resin. When the lubricant content is too high, appearance problems such as stains may occur on the surface of an automotive interior product prepared using the composite resin composition including the lubricant, so that the appearance quality may be reduced.

[0081] The heat stabilizer is not particularly limited as long as the automotive interior product prepared using the composite resin composition including the heat stabilizer can be prevented from being deformed due to high temperature. Preferably, the heat stabilizer may be a phenolic antioxidant.

[0082] The phenolic antioxidant may further include a hindered phenolic stabilizer having a crystallization temperature (Tm) of 110° C. to 130° C. As a specific example, the phenolic antioxidant may include tetrakis[ethylene-3-(3,5-di-tert-butyl-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, or a combination thereof.

[0083] The content of the heat stabilizer may be 0.01 to 10 parts by weight, specifically 0.1 to 5 parts by weight, based on 100 parts by weight of the composite resin. When the content of the heat stabilizer is too high, appearance problems such as stains may occur on the surface of an automotive interior product prepared using the composite resin composition including the heat stabilizer, so that the appearance quality may be reduced.

[0084] The ultraviolet absorber is not particularly limited as long as the automobile interior product prepared using the composite resin composition containing the ultraviolet absorber can be prevented from being deformed by light. Preferably, the ultraviolet absorber may be a benzotriazole compound, a triazine compound, or the like.

[0085] The triazine compound may be one or more selected from the following, for example, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, oxazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3 ,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, -3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-N-octyloxyphenyl)-1,3,5-triazine and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol.

[0086] The benzotriazole compound may be one or more selected from the following, for example, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-5'-hydroxyphenyl)-benzotriazole, 2-(2'-hydroxymethylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α-dimethylbenzylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dibutylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α-dimethylbenzylphenyl)benzotriazole, -tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2-N-benzotriazol-2-yl)phenol', 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol and 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol.

[0087] In order to improve light resistance while improving heat resistance under high load, the composite resin of the present disclosure may include one or more selected from triazine compounds having a weight average molecular weight of 400 g / mol or more and benzotriazole compounds having a weight average molecular weight of 400 g / mol or more.

[0088] As a specific example, the composite resin of the present disclosure may include one or more selected from the following: a triazine compound that can absorb ultraviolet light with a wavelength of 300nm to 400nm and a weight average molecular weight of 400g / mol to 600g / mol or 400g / mol to 500g / mol; and a benzotriazole compound that can absorb ultraviolet light with a wavelength of 270nm to 350nm and a weight average molecular weight of 400g / mol to 600g / mol or 400g / mol to 500g / mol. In this case, the physical properties are well balanced and the light resistance is further improved.

[0089] The ultraviolet absorber may be included in an amount of 0.01 to 5 parts by weight, specifically 0.05 to 3 parts by weight, based on 100 parts by weight of the composite resin. Within this range, physical properties are well balanced and light resistance is further improved.

[0090] The ultraviolet absorber may be included in an amount of 0.01 to 5 parts by weight, specifically 0.05 to 3 parts by weight, based on 100 parts by weight of the composite resin. Within this range, physical properties are well balanced and light resistance is further improved.

[0091] The lubricant, heat stabilizer and ultraviolet absorber may be contained in an amount of 0.1 to 5 parts by weight, preferably 1 to 3 parts by weight, based on 100 parts by weight of the polyester resin. In this case, an optimal balance between heat resistance and light resistance can be maintained.

[0092] The composite resin composition of the present disclosure may have a light resistance characteristic deviation (ΔE) represented by the following Equation 1 of 2.0 or less, specifically 1.0 or less, preferably 0.1 to 0.5. In this case, an optimal balance between heat resistance and light resistance may be maintained.

[0093] [Equation 1]

[0094] Lightfastness deviation = (glossiness of glossy sample - glossiness of embossed sample)

[0095] (In the equation, gloss is at 89±3℃, 50±5% relative humidity, 84MJ / m 2 The irradiation dose and 0.55±0.02W / m 2· nm (300nm to 400nm) irradiance is measured according to MS210-05, and

[0096] A glossy specimen was prepared using a mold mirror-finished with a grit size of 2,000 to 40,000 at an injection temperature of 230° C. to 250° C. and a mold temperature of 50° C., and an embossed specimen was prepared in the same manner as the above specimen except that a mold having an embossed pattern with a size of 15 μm to 21 μm formed on its surface was used.

[0097] Unless otherwise specified, glossiness may refer to a color difference change (ΔE) obtained according to the following Equation 2 after measuring respective colors of a glossy sample and an embossed sample.

[0098] [Equation 2]

[0099]

[0100] In order to obtain the light resistance characteristic deviation, the glossiness is measured according to the specular component include (SCI) method including specular reflection light according to MS210-05. The SCI evaluation method is different from the evaluation method close to the naked eye reflecting the SCE described below in that the SCI evaluation method evaluates the color of the material itself without considering the surface state.

[0101] Method for preparing composite resin composition

[0102] Hereinafter, a method for preparing the composite resin composition of the present invention is described. In describing the method for preparing the composite resin composition of the present invention, all the above details about the composite resin composition are included.

[0103] The method for preparing a composite resin composition disclosed herein includes, for example, feeding 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 wt % to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 wt % to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 wt % to 37 wt % of a polyester resin into an extruder, and melt-kneading and extruding the mixture, wherein the content (%) of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content (%) of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer.

[0104] As a specific example, the method for preparing a composite resin composition disclosed in the present invention includes: feeding 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 wt % to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 wt % to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 wt % to 37 wt % of a polyester resin into an extruder, and melt-kneading and extruding the mixture, wherein the content of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer is 27 wt % to 29 wt % based on the total weight of the copolymer, and the intrinsic viscosity of the polyester resin is 1.05 dl / g or more.

[0105] In the melt-kneading step, for example, the above-mentioned other additives may be contained.

[0106] The melt mixing and extrusion steps can be, for example, carried out using one or more selected from a single screw extruder, a twin screw extruder and a Banbury mixer, preferably a twin screw extruder. The melt mixing and extrusion steps can be carried out by uniformly mixing the components using an extruder and then extruding to obtain a composite resin composition in the form of pellets. In this case, mechanical property degradation and thermal property reduction are prevented, and excellent coating adhesion and appearance quality are provided.

[0107] The step of preparing pellets using an extrusion kneader can be carried out, for example, under the conditions of an extrusion temperature of 210° C. to 280° C., an extrusion rate of 30 kg / hr to 90 kg / hr and a screw rotation number of 200 rpm to 350 rpm, preferably under the conditions of an extrusion temperature of 210° C. to 250° C., an extrusion rate of 30 kg / hr to 70 kg / hr and a screw rotation number of 200 rpm to 300 rpm.

[0108] The pellets prepared after extruding the composite resin composition may be dried in a convection oven at 60° C. to 90° C. for more than 4 hours and then injection molded.

[0109] The injection molding may include the following steps: using an injection molding machine (ENGEL, 80 tons) to perform injection molding at an injection temperature of 240°C to 280°C, specifically 240°C to 260°C, a mold temperature of 40°C to 80°C, specifically 50°C to 70°C, and an injection rate of 10 mm / sec to 50 mm / sec, specifically 20 mm / sec to 40 mm / sec.

[0110] Additionally, an automotive interior product comprising the composite resin composition of the present invention is described. In describing an automotive interior product comprising the composite resin composition of the present invention, all of the above details regarding the composite resin composition are included.

[0111] Automotive interior products

[0112] Since the composite resin composition of the present invention is fully optimized using the above components, the composite resin composition can be effectively used in automotive interior products requiring molding performance, mechanical properties, heat resistance under low load, heat resistance under high load, and chemical resistance.

[0113] The automotive interior product can be manufactured by a method commonly used in the art. For example, using a melt-kneaded material or pellets of the composite resin composition according to the present invention, or a sheet (plate) molded using the melt-kneaded material or pellets as a raw material, injection molding, injection compression molding, extrusion molding, sheet casting, press molding, pressure forming, heat bending, compression molding, calendaring, rotational molding, etc. can be applied.

[0114] The composite resin composition comprising the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer, the aromatic vinyl compound-vinyl cyanide compound copolymer, the polyester resin and the additives of the present disclosure is fed in the following manner, for example, at a supply rate of 50 kg / h to a twin-screw extruder ( L / D: 42, SMPlatek equipment) and then melt-mixed and extruded to prepare pellets.

[0115] The pellets were fed into an injection molding machine to produce automotive interior products.

[0116] In order to indirectly confirm the physical properties of the automotive interior product, the pellets were injected using an injection molding machine (ENGEL, 80 tons) at an injection temperature of 250° C., a mold temperature of 60° C., and an injection rate of 30 mm / sec to manufacture test specimens according to ISO standards.

[0117] The flow index (melt flow rate) of the manufactured test piece measured at 250° C. under a load of 5 kg according to ISO 1133 may be, for example, 25 g / 10 min or more, specifically, 25 g / 10 min to 27 g / 10 min.

[0118] In addition, the notched Izod impact strength of the specimen measured at 23° C. according to ISO 180 / 1A may be, for example, 14 kJ / m 2 Above, specifically, 14 kJ / m 2 Up to 15kJ / m 2 .

[0119] In addition, the tensile strength of the test piece measured at a speed of 5 mm / min according to ISO 527 may be, for example, 49 MPa or more, specifically, 53 MPa to 60 MPa.

[0120] In addition, the flexural strength of a 1 / 8 inch specimen measured at a speed of 2 mm / min using SPAN 64 according to ISO 178 may be, for example, 61 MPa or more, specifically 63 to 64 MPa, and the flexural modulus thereof may be 1950 MPa or more, specifically 2000 to 2070 MPa.

[0121] In addition, the sample may have a high load heat deformation temperature (HDT) measured under a load of 1.82 MPa according to ISO 75 of 75°C or more, specifically, 76°C to 77°C.

[0122] In addition, the low load heat deformation temperature (HDT) of the test piece measured under a load of 0.45 MPa according to ISO 75 may be 93°C or higher, specifically, 95°C to 96°C.

[0123] In addition, the density of the sample measured according to ISO 1183 can be 1.10 g / cm 3 Above, specifically, 1.10 g / cm 3 Up to 1.12g / cm 3 .

[0124] In addition, the L* value of the sample measured by the specular reflection excluding light (SCE) reflection LAB colorimeter, which is an evaluation method close to the naked eye by excluding specular reflection light and measuring only scattered light according to ISO 7724, was 16.22 or less, specifically 11.00 to 13.77. Here, as the L* value approaches 0, it approaches black, and the degree of gas generation during injection is reduced, which indicates that the appearance quality is excellent.

[0125] In addition, when a specimen having the same size (length: 165 mm, width: 19 mm, thickness: 3.2 mm) as the tensile strength measurement specimen according to ASTM D638 was fixed to a jig having a stress of 2.0% according to an environmental stress cracking (ESC) test according to ISO 4599, 25 μl of a mixed solution containing isoamyl acetate, limonene, and linalool at a volume ratio of 4:1:1 was applied to the specimen using a micropipette, and then, after 2 hours, the occurrence of cracks or cracks was observed, and the specimen had no cracks or cracks. This indicates that the specimen has excellent chemical resistance.

[0126] The a value of the sample measured with a SCE reflection LAB colorimeter may be -0.25 to -0.55 and the b value may be -3.52 to -4.03, which is an evaluation method close to the naked eye by excluding specular reflected light and measuring only diffuse light according to ISO 7724.

[0127] The automotive interior product may specifically be a floor control seat front tray or a cup holder, but is not limited to a specific type.

[0128] That is, the composite resin composition according to one embodiment of the present invention includes a polyester resin, a predetermined emulsion-polymerized copolymer, a bulk-polymerized copolymer, and a thermoplastic copolymer, and therefore, unlike existing automotive interior products, an automotive interior product manufactured using the composition exhibits improved heat resistance and chemical resistance, thereby satisfying a balance between physical properties such as mechanical properties, fluidity, and light resistance, and provides excellent product reliability and appearance quality.

[0129] In describing the composite resin composition, the method for preparing the composite resin composition, and the automotive interior product including the composite resin composition of the present invention, other conditions or equipment not explicitly described may be appropriately selected within the range generally practiced in the art and are not particularly limited.

[0130] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments described herein.

[0131] [Example]

[0132] Examples 1 to 5, Comparative Examples 1 to 9, Reference Examples 1 and 2: Preparation of Composite Resin Compositions

[0133] The following starting materials were used in the examples.

[0134] A-1) Polybutylene terephthalate: Intrinsic viscosity (IV): 1.0

[0135] A-2) Polybutylene terephthalate: Intrinsic viscosity (IV): 1.2

[0136] B) Emulsion polymerized diene rubber-styrene-acrylonitrile (butadiene 60% by weight, styrene 30% by weight, acrylonitrile 10% by weight)

[0137] C) Bulk polymerized diene rubber-styrene-acrylonitrile (butadiene 11% by weight, styrene 62% by weight, acrylonitrile 27% by weight)

[0138] D-1) Styrene-acrylonitrile (styrene 72 wt%, acrylonitrile 28 wt%, weight average molecular weight 133,000 g / mol)

[0139] D-2) Styrene-acrylonitrile (styrene 76 wt%, acrylonitrile 24 wt%, weight average molecular weight 121,000 g / mol)

[0140] E) Amide lubricant

[0141] F) Heat stabilizer (high phenolic antioxidant)

[0142] G) Benzotriazole compounds (weight average molecular weight: 448 g / mol)

[0143] The raw materials summarized in Table 1 below were mixed to prepare a composite resin composition, and then the composite resin composition having uniform dispersion was manufactured into the form of pellets by extrusion. Next, the pellets were heated and injected into a mold, and then cooled. The cooled pellets were manufactured into test specimens to be used as automotive interior products in the injection process of manufacturing parts.

[0144] Specifically, the components summarized in Table 1 below were mixed using a mixer and then fed into a twin-screw extruder ( L / D: 42, barrel temperature: 230° C., extrusion rate: 50 kg / hr, screw rotation number: 250 rpm, SMPlatek equipment), and extruded for 1 to 3 minutes to produce composite resin composition pellets.

[0145] The prepared pellets were dried in a convection oven at 80°C for more than 4 hours and then injected using an injection molding machine (ENGEL, 80 tons) under the conditions of an injection temperature of 260°C, a mold temperature of 60°C and an injection rate of 30 mm / sec to manufacture ISO test specimens.

[0146] [Table 1]

[0147]

[0148] For reference, the total wt % of raw materials A-1 to G summarized in Table 1 is 100 wt %.

[0149] Test example: Physical performance evaluation of automotive interior product samples

[0150] Physical properties were evaluated for the automotive interior product samples manufactured according to Examples 1 to 5, Comparative Examples 1 to 9, and Reference Examples 1 and 2. The evaluation criteria were as follows.

[0151] - Flowability (melt flow rate): according to ISO 1133 (250°C, 5kg)

[0152] -Impact strength (IZOD): According to ISO 180 / 1A (notched, 23°C)

[0153] -Tensile strength: According to ISO 527 (50mm / min)

[0154] - Flexural strength, flexural modulus: according to ISO 178 (1 / 8 inch, SPAN 64, speed: 2 mm / min)

[0155] -Heat deformation temperature: According to ISO 75 (high load: 1.82MPa, low load: 0.45MPa)

[0156] Density: measured according to ISO 1183

[0157] - Chemical resistance: Environmental stress cracking (ESC), a specimen having the same size (length: 165 mm, width: 19 mm, thickness: 3.2 mm) as the tensile strength measurement specimen according to ASTM D638 was fixed to a fixture with a stress of 2.0% according to ISO 4599, 25 μl of a fragrance (a mixed solution containing isoamyl acetate, limonene, and linalool in a volume ratio of 4:1:1) was applied to the specimen using a micropipette, and then, after 2 hours, the generation of cracks or cracks was observed with the naked eye. When no cracks or cracks were generated, it was marked as "normal". When cracks or cracks were generated, it was marked as "crack".

[0158] - Lightfastness deviation (ΔE): The lightfastness deviation between the glossy sample and the embossed sample was measured according to MS210-05 using a measurement method including specular reflection light (SCI) (including specular reflection light, thereby evaluating the color of the material itself regardless of the surface state) at a temperature of 89±3°C, a relative humidity of 50±5%, and a temperature of 84MJ / m 2 The irradiation dose and 0.55±0.02W / m 2 ·nm (300nm to 400nm) is obtained from the following Equation 1. When the calculated value exceeds 2.0, it is determined that the light resistance is poor.

[0159] [Equation 1]

[0160] Lightfastness deviation = (glossiness of glossy sample - glossiness of embossed sample)

[0161] Here, the glossy specimens were manufactured by using a mold subjected to mirror surface treatment of 2,000 to 40,000 grit under the conditions of an injection temperature of 230° C. to 250° C. and a mold temperature of 50° C., and the embossed specimens were manufactured in the same manner as the glossy specimens by using a mold for forming an embossed shape having a size of 15 μm to 21 μm on the surface of the specimen.

[0162] In addition, the color of each of the glossy sample and the embossed sample was measured using a Hunter Lab colorimeter, and the color difference change (ΔE) of each sample was obtained by the following Equation 2.

[0163] [Equation 2]

[0164]

[0165] -Laboratory colorimetric test: The L value, a value, and b value of the sample were measured using a measurement method excluding specular reflected light (SCE) (this is an evaluation method close to the naked eye by excluding specular reflected light and measuring only diffuse light) according to ISO 7724. As the L* value approaches 0, it approaches black, and the degree of gas generation during injection decreases, this indicates that the appearance quality is excellent.

[0166] The results measured according to the evaluation criteria are summarized in Table 2 below.

[0167] [Table 2]

[0168]

[0169]

[0170]

[0171] Referring to Table 2, it can be confirmed that the composite resin compositions according to Examples 1 to 5 of the present invention provide excellent impact strength, flexural modulus, high-load heat deformation temperature, and light resistance (light resistance characteristic deviation) while achieving a density within an appropriate range, and therefore, the automotive interior products manufactured using the composite resin compositions have excellent chemical resistance, high-load heat resistance, and light resistance while substantially satisfying physical properties such as impact strength, tensile strength, and flexural strength, and exhibit excellent product reliability and appearance quality due to low gas generation during injection.

[0172] On the other hand, it was confirmed that, compared with Examples 1 to 5, in the case of Comparative Example 2 which did not include the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the remaining three components were used in excess, the impact strength was significantly inferior.

[0173] In addition, it can be confirmed that compared with Examples 1 to 5, in the case of Comparative Examples 3 to 5 where the respective amounts of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the vinyl cyanide compound-aromatic vinyl compound are outside the scope of the present invention, the impact strength, flow index, etc. are inferior.

[0174] Specifically, it can be confirmed that, in the case of Comparative Example 5 in which the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is used in a very small amount, the flow index is lowered and the flexural strength, flexural modulus and heat deformation temperature under high load are poor compared with Examples 1 to 5.

[0175] In addition, it can be confirmed that, compared with Examples 1 to 5, in the case of Comparative Example 6 in which the amount of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer used exceeds the scope of the present invention and the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is not used, the flow index and the bending modulus are poor.

[0176] In addition, it can be confirmed that, compared with Examples 1 to 5, in the case of Comparative Example 7, in which the amount of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is outside the scope of the present invention, the amount of the aromatic vinyl compound-vinyl cyanide compound copolymer is less than the scope of the present invention, and the amount of the polyester resin is excessive, the flow index, flexural strength and flexural modulus are all poor.

[0177] In addition, it was confirmed that in the case of Comparative Example 8 in which the amount of the aromatic vinyl compound-vinyl cyanide compound copolymer used exceeded the range of the present invention, the flexural strength, flexural modulus, heat deformation temperature under high load and chemical resistance were inferior to those of Examples 1 to 5.

[0178] In addition, it can be confirmed that in the case of Comparative Example 9 in which the polyester resin is used in excess and the aromatic vinyl compound-vinyl cyanide compound copolymer is used in a small amount, the flexural strength, flexural modulus, heat deformation temperature under low load and heat deformation temperature under high load are all inferior compared with Examples 1 to 5.

[0179] In addition, it can be confirmed that, compared with Examples 1 to 5, in the case of Comparative Example 10, in which the amount of the polyester resin used exceeds the scope of the present invention and the amounts of the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer and the aromatic vinyl compound-vinyl cyanide compound copolymer are less than the scope of the present invention, the flexural strength, flexural modulus, heat deformation temperature under low load, and heat deformation temperature under high load are all poor.

[0180] In addition, it was confirmed that, compared with Examples 1 to 5, in Reference Example 1 using a polyester resin having an intrinsic viscosity outside the range of the present invention, the impact strength and the flexural modulus were reduced.

[0181] It was also confirmed that, compared with Examples 1 to 5, in Reference Example 2 in which the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer was smaller than the range of the present invention, the impact strength was inferior.

[0182] That is, the composite resin composition according to one embodiment of the present invention includes a polyester resin and an emulsion-polymerized copolymer, a bulk-polymerized copolymer, and a thermoplastic copolymer containing a specific component in a predetermined content, and therefore, an automotive interior product manufactured using the composition exhibits improved heat resistance and chemical resistance, thereby satisfying a balance between physical properties such as mechanical properties, fluidity, and light resistance, and provides excellent product reliability and appearance quality.

Claims

1. A composite resin composition comprising: 15 to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 to 37 wt % of a polyester resin, in, The content of the aromatic vinyl compound contained in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content of the aromatic vinyl compound contained in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer. Wherein, based on the total weight of the aromatic vinyl compound-vinyl cyanide compound copolymer, the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer is 26 wt % to 29 wt %, The polyester resin has an intrinsic viscosity of 1.1 dl / g to 1.3 dl / g.

2. The composite resin composition according to claim 1, wherein A weight ratio of the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer to the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is 1:1.37 to 1.

66.

3. The composite resin composition according to claim 1, wherein The polyester resin is one or more selected from polybutylene terephthalate (PBT), polyethylene adipate (PEA), polybutylene succinate (PBS), polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT) and polyethylene naphthalate (PEN).

4. The composite resin composition according to claim 1, wherein The composite resin composition has an L* value of 14.00 or less, the L* value being obtained by measuring light reflected from a sample obtained by SCE using a LAB colorimetric system.

5. The composite resin composition according to claim 1, wherein The first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer comprises: 40 wt % to 80 wt % of a diene rubber polymer having an average particle size of 100 nm to 500 nm, 10 wt % to 40 wt % of an aromatic vinyl compound and 1 wt % to 20 wt % of a vinyl cyanide compound.

6. The composite resin composition according to claim 1, wherein The second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer comprises: 5 to 20 wt % of a diene rubber polymer having an average particle size of 800 to 10,000 nm, 50 to 85 wt % of an aromatic vinyl compound, and 10 to 30 wt % of a vinyl cyanide compound.

7. The composite resin composition according to claim 1, wherein The aromatic vinyl compound-vinyl cyanide compound copolymer includes 71 to 72 wt % of an aromatic vinyl compound and 28 to 29 wt % of a vinyl cyanide compound, and has a weight average molecular weight of 130,000 to 180,000 g / mol.

8. The composite resin composition according to claim 1, wherein The composite resin composition has a flow index measured at 250° C. under a load of 5 kg according to ISO 1133 of 25 g / 10 min or more.

9. The composite resin composition according to claim 1, wherein The Izod impact strength of the composite resin composition measured at 23°C according to ISO 180 / 1A is 14 kJ / m 2 above.

10. The composite resin composition according to claim 1, wherein The flexural modulus of a 1 / 8 inch test specimen manufactured using the composite resin composition measured at a speed of 2 mm / min according to ISO 178 is 1950 MPa or more.

11. The composite resin composition according to claim 1, wherein The composite resin composition has a high-load heat resistance of 75° C. or higher measured at 1.82 MPa according to ISO 75.

12. A method for preparing a composite resin composition, the method comprising: 15 wt % to 20 wt % of a first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 9 to 15 wt % of a second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer; 32 to 40 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer; and 29 to 37 wt % of a polyester resin are fed into an extruder, followed by melt-kneading and extruding, The content of the aromatic vinyl compound in the first vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer is less than the content of the aromatic vinyl compound in the second vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer. Wherein, based on the total weight of the aromatic vinyl compound-vinyl cyanide compound copolymer, the content of the vinyl cyanide compound contained in the aromatic vinyl compound-vinyl cyanide compound copolymer is 26 wt % to 29 wt %, The polyester resin has an intrinsic viscosity of 1.1 dl / g to 1.3 dl / g.

13. An automobile interior product, the automobile interior product being manufactured using the composite resin composition according to any one of claims 1 to 11.

14. The automotive interior product according to claim 13, wherein: The automotive interior product is a floor-mounted front tray or a cup holder.

Citation Information

Patent Citations

  • Improved bumper system

    KR1020210059760A

  • Connector to prevent kinking of fire hose

    KR1020220024264A

  • Thermoplastic resin composition and molded article comprising same

    CN107001746A

  • Thermoplastic resin composition having improved impact resistance

    KR1020150078316A